Unmanaged climate risks to spent fuel from U.S. nuclear power plants: The case of sea-level rise. (February 2020) - Jenkins, Lisa Martine; Alvarez, Robert; Jordaan, Sarah Marie
Abstract: Climate change and its accompanying sea-level rise is set to create risks to the United States' stockpile of spent nuclear fuel, which results largely from nuclear power. Coastal spent fuel management facilities are vulnerable to unanticipated environmental events, as evidenced by the 2011 tsunami-related flooding at the Fukushima plant in Japan. We examine how policy-makers can manage climate risks posed to the coastal storage of radioactive materials, and identify the coastal spent fuel storage sites that will be most vulnerable to sea-level rise. A geospatial analysis of coastal sites shows that with six feet of sea-level rise, seven spent fuel sites will be juxtaposed by seawater. Of those, three will be near or completely surrounded by water, and should be considered a priority for mitigation: Humboldt Bay (California), Turkey Point (Florida), and Crystal River (Florida). To ensure policy-makers manage such climate risks, a risk management approach is proposed. Further, we recommend that policy-makers 1) transfer overdue spent fuel from cooling pools to dry casks, particularly where located in high risk sites; 2) develop a long-term and comprehensive storage plan that is less vulnerable to climate change; and 3) encourage international nuclear treaties and standards to take climate change into account. Highlights: Climate change will result in new risks to nuclear power operations. Spent fuel sites will be subject to risks from sea-level rise. A long-term spent fuel management plan is needed to mitigate risks. Short-term solutions to mitigate risks are recommended.